Management competencies of clinical managers at public hospitals in Gauteng, South Africa: implications for coaching - Sithole, Mperekeng Bekani Naumi (My University, 2017)
Introduction Public hospitals are complex environments in which healthcare leaders are required to lead effectively in order to provide quality service delivery. The issue is: are clinical managers working in Gauteng hospitals competent to lead? This study measures the competency of clinical managers in public hospitals and considers how coaching can be used to close the competency gap in Gauteng public hospitals. Coaching has been identified as one of the appropriate developmental tools to enhance the skills’ gap of top managers in organisations (West & Milan, 2001). In this study, coaching has been considered to be an appropriate learning and developmental tool to enhance skills for these managers. Methods A self-administered questionnaire was used to conduct the survey among clinical managers in the hospitals in Gauteng. Participants were asked to rate the required management competencies and their proficiency levels against nine management competency categories which include: leadership, communication, life-long learning, consumer responsiveness, political and health environment, conceptual skills, results management, resource management, compliance with standards and coaching in improving management competencies .Likert-scale data was used to measure the top managers’ perceptions of the important competencies required for effective service delivery and their level of proficiency with those competencies. Results Findings show that there is significant gap in management competency of clinical managers, which indicates the need for further development of managers. Most clinical managers’ have a perception that coaching has a role in enhancing their competency gap. Literature supports coaching as a leadership development tool for closing the competency gap of clinical managers. Conclusion There is significant gap in the public health sector managers’ competency level. There is a need for appropriate and further training and development to address the skills gap. There is need to strengthen management capacity to support the strategy of improved and sustainable healthcare service delivery. Coaching is the appropriate leadership developmental and supportive tool to enhance the skills needed by clinic managers.
Thesis (M.M. (Business Executive Coaching))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Wits Business School, 2017.
Keywords: Hospitals--South Africa--Administration; Executive coaching--South Africa; Employees--Training of--South Africa